APPLICATION OF HYPOCHLORITE SODIUM IN INTEGRATED TREATMENT UROGENITAL CHLAMIDIOSIS - M. E. VENGERENKO; G. A. PENJOYAN; V. V. PONOMAREV; V. V. ARTIUSHKOV; A. A. ZHUYKO (Кубанский научный медицинский вестник, 2018)
Aim. Assess some indicators of cellular and humoral immunity in order to achieve maximum efficacy in the treatment of urogenital chlamydia (UGH) in the combined use of sodium hypochlorite.Materials and methods. The object of the clinical study was 54 women with verified diagnosis of UGH, 30 of them were included in the treatment regimen, and 24 with furatsilin. Comprehensive examination of patients included: a detailed study of the history, the main complaints and the results of gynecological examination, performing a microscopy of the vaginal smear (on the 1st day of admission, on the 6th day after the vaginal sanitation and at the end of treatment). PCR diagnostics and immunoassay were performed before and after treatment, according to these criteria, the effectiveness of therapy was evaluated.Results. Chronic course of the disease is recorded in 100% of women, in the anamnesis of 37% of patients – chronic adnexitis, metroendometritis and colpitis of various etiologies. Of the women who turned to us for help (100%), 82% of the patients complained of abundant vaginal discharge, 27% – of dyspareunia, 19% of dysuria and itching of the external genitalia. Only 8% of the women examined did not make any complaints. 76% of the 30 patients who were initially examined had hyperemia of the vaginal mucosa. In the vaginal smear of women suffering from chlamydia, a significant proportion of leukocytes was found (the minimum value is 15,3 in n/sp, the maximum – 19,2 in n/sp). Scheme of treatment for chlamydia is provided for intravaginal sanitation with sodium hypochlorite. In all the examined patients, its tolerance was positive, as a result, the microbiocenosis of the vagina improved due to the elimination of pathogenic and opportunistic microorganisms. The reliability of the clinical effect was confirmed before antibiotics were prescribed.Conclusion. After the combined use of the sodium hypochlorite in the treatment of chlamydia, the total number of neutrophilic granulocytes and T-lymphocytes, the immunoregulatory index, the relative concentration of cells expressing the activation markers and the normalization of the total content of the main classes of immunoglobulins increase, which indicates the processes of functional recovery in the main parts of the immune system.